Study of Zuckerkandl Tubercle: Its Morphology and Associated Implications - Singh, Rajani (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
Thyroid gland is a very important gland of the human body as it is involved in regulating basal metabolism, psychosomatic growth of the body, and calcium metabolism. The thyroid gland exhibits a lot of variations in relation to its lobes, arterial supply, and nerve supply. Along the same lines, sometimes comparatively a less known structure called Tubercle of Zuckerkandl is found to be associated with the thyroid gland. The Tubercle of Zuckerkandl is a posterior or posterolateral extension of normal thyroid tissue. It is found to be related to the recurrent laryngeal nerve, the inferior thyroid artery, Berry's ligament, and the parathyroid glands. Of these relations, association of the tubercle with the recurrent laryngeal nerve and the parathyroid glands is very important during thyroid surgery. The recurrent laryngeal nerve innervates laryngeal muscles and laryngeal mucosa and if a recurrent laryngeal nerve is injured, it may lead to loss of voice and anaesthesia of the larynx. The parathyroid glands regulate calcium metabolism and if this gland is damaged it may lead to fatal conditions like tetany. Hence preservation of the recurrent laryngeal nerve and the parathyroid glands is very essential. The Tubercle of Zuckerkandl is an important landmark in identifying these two structures during thyroid surgery. Hence the study of the Tubercle of Zuckerkandl and its variant relations to the recurrent laryngeal nerve and the parathyroid glands is very important to achieve uneventful thyroid surgery. Considering so much significance of this anatomical structure, the study has been carried out. The aim of the study is to consolidate information on normal anatomy as well as the variant location and varied relations of the Tubercle of Zuckerkandl to the recurrent laryngeal nerve and the parathyroid glands and to elucidate implications associated with it. The literature was explored using databases like PubMed, SciELO, Google Scholar, and Midline.